Heart Rate and Motion Detection on Swimmers Simultaneous monitoring of heart rate and motion of swimmers - Sarwe, Anna (My University, 2014)
The use of pulse oximetry in measuring heart rates is well established. In this project the technique is applied in conjunction with a simple FFT (Fast Fourier Transform) treatment to the measuring of heart rates on swimmers using the MORES sensor developed by CiS Forschungsinstitut fur Mikrosensorik und Photovoltaik GmbH in Erfurt. Movement data is collected from an IMU (Inertial Measurement Unit) and fused using a complementary filter. It is found that due to the high noise ratio, poor performance of supporting hardware and immaturity of the oximetry sensor that the heart rate measurement gave unsatisfactory results. The IMU gives the expected data and the fusing algorithms perform as intended. Integration of accelerometer data for the acquisition of velocity and position is proven not to work.
Keywords: Grundläggande vetenskaper; Energi; Fysik; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Basic Sciences; Energy; Physical Sciences; Sustainable Development; Innovation & Entrepreneurship